ASSOCIATION OF UDDER BIOMETRY AND SKIN THICKNESS WITH MILK YIELD IN KANKREJ AND CROSSBRED COWS - Kshatriya, P S; Trivedi, M M; Dhami , A J (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Relationship between biometry of udder and skin thickness with milk yield was studied in 22 Kankrej and 26 crossbred (¼ HF x ¼ Jersey x ½ Kankrej) cows. Average evening milk yield on the test day was nonsignificantly higher in crossbred cows (3.52 kg) than the Kankrej cows (2.84 kg). Average udder length, width and depth in crossbred cows were 20.73, 23.31 and 8.00 inches, respectively. Corresponding values in Kankrej cows were 21.45, 23.09 and 7.77 inches. The skin thickness at all the three sites i.e. at neck, behind elbow and at flank was higher in Kankrej (7.86, 6.59 and 8.77 mm) than the crossbred cows (7.23, 5.46 and 7.00 mm, resp.). Correlation coefficients of milk yield with udder length, width and depth were positive and highly significant (P<0.01) in both the genetic groups. Highly significant negative correlations (P<0.01) were found between skin thickness at all the three sites and milk yield in both the genetic groups. It was concluded that both biometry of udder and skin thickness were related to milk yield and therefore could be considered as one of the criteria for selection of dairy cows.